Formation of legal consciousness among young people (Zien Journal of Social Sciences and Humanities, 2022)
Formation Of Legal Consciousness In Our Society, Formation Of Legal Consciousness Among Young People And Prevention Of Offenses Between Them, Increasing Legal Culture Serves Understanding The Essence Of Laws